Plasma lipid profile and leptin concentration in super-obese children - Aryono Hendarto; Sri Sudaryati Nasar; Damayanti Rusli Sjarif (Indonesian Pediatric Society, 2007)
Background Leptin induced weight loss is completely specificfor adipose tissue loss, whereas food restriction result in both lossof adipose tissue and lean body mass in mammals. Most obeseperson has high endogenous leptin levels, indicating leptinresistance. There has been lack of data regarding plasma leptinlevel in Indonesian obese children.Objective This study was aimed to investigate the plasma leptinlevel and lipid profile in super-obese children.Methods This was a cross sectional study performed in PediatricOut Patient Clinic Mangunkusumo Hospital and Private Women& Children Hospital in Eastern part of Jakarta. Super-obese isdefined as children with BMI above 97 centiles CDC 2000 chart.Blood sample was obtained from all subjects, consisted ofperipheral blood picture, lipid profiles and leptin level.Results Seventy nine super-obese children were eligible with ageranged between 12 months and 180 months and mean of age was84.9 months (SD 36.8). More than 60% subjects had high LDLcholesterol, while 19% had low HDL level. The lowest leptinblood level was 2.877 Î¼ g/dL, while the highest was 70.430 Î¼ g/dL(mean 23.990; SD 12.726). Forty five subjects, all boys, hadincreased plasma leptin level.Conclusions In super-obese children, most of the subjectexperienced hyperlipidemia (LDL cholesterol) followed byhypertriglyceridemia. There was small number of low HDLcholesterol found. Super-obese girls had normal serum leptin level,in contrast, more than 60% super-obese boys had elevated serumleptin level.